A Study on Logical Fallacies in Argumentation on Debate Made by English Debate Society Members of UNESA (RETAIN, 2017)
A Study on Logical Fallacies in Argumentation on Debate Made by English Debate Society Members of UNESA Sazi Ajeng Ayu Virginia English Education, Language and Art Faculty, State University Surabaya sazivirginia0303@g,mail.com Esti Kurniasih, S.Pd, M.Pd English Education Department, Faculty of Language and Art, State University of Surabaya Estikurniasih@unesa.ac.id Abstrak Sebagai anggota debat bahasa inggris (EDS) UNESA, para pelaku debat seharusnya mampu untuk awas dan sadar tentang kesalahan pada logika berfikir yang mampu mengurangi kualitas penampilan dalam berdebat. Maka dari itu, penelitian ini ditujukan untuk menginvestigasi kesalahan logika pada argument debat dibuat oleh EDS UNESA. Penelitian ini adalah penelitian deskriptif dan jenis data yang di kumpulkan adalah kualitatif. Subyek penelitian ini adalah tiga anggota EDS UNESA. Agar dapat menjawab penelitian pertanyaan, subyek di rekam ketika sedang melakukan latihan debat. Kemudian, peneliti melakukan observasi note dan wawancara dengan mengunakan perekam suara dan panduan wawancara sebagai instrument penelitian. Berdasarkan hasil penelitian, terdapat beberapa kesalahan logika yang ditemukan pada cara anggota EDS UNESA menyusun argument. Kesalahan logika yang ditemukan adalah problematic premise, red hearing fallacy, irrelevant reason, two wrong fallacy, begging the question, fault analogy, dan fallacy incompatibility. Oleh sebab itu, peneliti menyarankan untuk lebih banyak belajar tentang kesalahan logika dan melakukan banyak latihan. Saran untuk proses belajar mengajar pada kelas menulis argument dan debat adalah agar para pembimbing agar member perhatian lebih kepada logika berfikir dan meminta siswa-siswi untuk lebih memahami pengetahauan awal tentang bukti dan klaim agardapat menciptakan argument yang lebih baik. Kata Kunci : Kesalahan Logika, Argument, Debat, English Debate Society Abstract As members of English Debate Society (EDS) UNESA, debaters need to be aware of and conscious about the logical fallacy that can degrade the performance of debating. Therefore, this research was aimed to investigate the logical fallacy on debate argumentation made by EDS UNESA. This research is descriptive research and the data collected was of the qualitative type. The subjects of the study were three members of EDS UNESA. In order to find the answer, students were recorded when they were conducting training. Then, the researcher conducted observation field notes and interview by using audio recorder and interview guideline as the instrument. Based on the analysis, there were several types of logical fallacy found. They are problematic premise, red hearing fallacy, irrelevant reason, two wrong fallacy, begging the question, fault analogy, and fallacy incompatibility. Moreover, some factors that caused the debaters create fallacy are the Level of understanding toward concept of logical fallacy, lack of reading and amount of debate practice. Therefore, the researcher suggests debaters to learn more regarding logical fallacy and do more practices. Suggestion for teaching learning process in argumentative writing and speaking for debate class the lecturers can give more attention in logical fallacy and ask students to be more aware by analyzing the prior information regarding the evidence and provide sufficient explanation to create link between evidence and claim in order to create better quality of argumentation. Keyword: Logical fallacy, argumentation, debate, English Debate Society